Celecoxib-mediated reduction of prostanoid release in Hoffa's fat pad from donors with cartilage pathology results in an attenuated inflammatory phenotype. Issue 5 (May 2018) - Timur, U.T.; Caron, M.M.J.; Bastiaansen-Jenniskens, Y.M.; Welting, T.J.M.; van Rhijn, L.W.; van Osch, G.J.V.M.; Emans, P.J.
Summary: Objective: The Hoffa's fat pad (HFP) is an intra-articular adipose tissue which is situated under and behind the patella. It contains immune cells next to adipocytes and secretes inflammatory factors during osteoarthritis (OA). In this study, we compared the release profile of prostanoids, which are involved in inflammation, of HFP from OA patients vs patients with a focal cartilage defect (CD) without evidence for OA on MRI and investigated the prostanoid modulatory anti-inflammatory action of celecoxib on HFP. Design: Prostanoid release was analyzed in conditioned medium of HFP explant cultures from 17 osteoarthritic patients and 12 CD patients, in the presence or absence of celecoxib. Furthermore, gene expression of COX enzymes and expression of genes indicative of a pro-inflammatory or anti-inflammatory phenotype of HFP was analyzed. Results: Prostanoid release by HFP from knee OA patients clustered in two subgroups with high and low prostanoid producers. HFP from high prostanoid producers released higher amounts of PGE2, PGF2α and PGD2 compared to HFP from CD patients. PGE2 release by OA HFP was positively associated with expression of genes known to be expressed by M1 macrophages, indicating a role for macrophages. Celecoxib modulated prostanoid release by HFP, and also modulated the inflammation ratio towards a more favorable anti-inflammatory M2 phenotype, most effectively in patients with higher prostanoid release profiles. Conclusion: In knee OA patients with inflamed HFP's, celecoxib may exert positive effects in the knee joint via decreasing the release of prostanoids produced by the HFP and by favorably modulating the anti-inflammatory marker expression in HFP.